Drosophila Skp1 Homologue SkpA Plays a Neuroprotective Role in Adult Brain - Dabool, Lital (iScience, 2020)
Skp1, a component of the ubiquitin E3 ligases, was found to be decreased in the brains of sporadic Parkinson's disease (PD) patients, and its overexpression prevented death of murine neurons in culture. Here we expose the neuroprotective role of the Drosophila skp1 homolog, skpA, in the adult brain. Neuronal knockdown of skpA leads to accumulation of ubiquitinated protein aggregates and loss of dopaminergic neurons accompanied by motor dysfunction and reduced lifespan. Conversely, neuronal overexpression of skpA reduces aggregate load, improves age-related motor decline, and prolongs lifespan. Moreover, SkpA rescues neurodegeneration in a Drosophila model of PD. We also show that a Drosophila homolog of FBXO7, the F Box protein, Nutcracker (Ntc), works in the same pathway with SkpA. However, skpA overexpression rescues ntc knockdown phenotype, suggesting that SkpA interacts with additional F box proteins in the adult brain neurons. Collectively, our study discloses Skp1/SkpA as a potential therapeutic target in neurodegenerative diseases.